Is There a General Factor of Spiritual Intelligence? Factorial Validity of the Polish Adaptation of Spiritual Intelligence Self-Report Inventory - Atroszko, Paweł A.; Balcerowska, Julia M.; Skrzypińska, Katarzyna (2021)
In recent years, spirituality and the meaning of life are becoming increasingly important variables in the study of well-being, health, and happiness. The concept of spiritual intelligence (SI) was suggested as a potentially significant construct expanding our understanding of psychological determinants of human functioning. The aim of this paper was to investigate the factorial validity of the Spiritual Intelligence Self-Report Inventory (SISRI; King, 2008) in the context of research on a general factor of spiritual intelligence as a psychological construct. The SISRI was administered to 833 adults in Poland. A four-factor solution with one second-order factor of spiritual intelligence provided an inadequate solution. A four-factor solution with correlated factors and a reduced number of items provided an adequate fit to the data. It is concluded that so far, no data are supporting a single factor of SI measured by SISRI-24, and previous studies, including the original study, show that the measurement with this scale is highly problematic. Without a strong theory and proper measurement, the development of this highly promising area of research may be hindered.
Keywords: Factor analysis; Measurement; Spirituality; Statistics; Validity